Uncoupling the Trade-Off between Somatic Proteostasis and Reproduction in Caenorhabditis elegans Models of Polyglutamine Diseases - Shemesh, Netta; Shai, Nadav; Meshnik, Lana; Katalan, Rotem; Ben-Zvi, Anat (Frontiers in Molecular Neuroscience, 2017)
Caenorhabditis elegans somatic protein homeostasis (proteostasis) is actively remodeled at the onset of reproduction. This proteostatic collapse is regulated cell-nonautonomously by signals from the reproductive system that transmit the commitment to reproduction to somatic cells. Here, we asked whether the link between the reproductive system and somatic proteostasis could be uncoupled by activating downstream effectors in the gonadal longevity cascade. Specifically, we examined whether overexpression of lipl-4 (lipl-4(oe)), a target gene of the gonadal longevity pathway, or increase in arachidonic acid (AA) levels, associated with lipl-4(oe), modulated proteostasis and reproduction. We found that lipl-4(oe) rescued somatic proteostasis and postponed the onset of aggregation and toxicity in C. elegans models of polyglutamine diseases. However, lipl-4(oe) also disrupted fatty acid transport into developing oocytes and reduced reproductive success. In contrast, diet supplementation of AA recapitulated lipl-4(oe)-mediated proteostasis enhancement in wild type animals but did not affect the reproductive system. Thus, the gonadal longevity pathway mediates a trade-off between somatic maintenance and reproduction, in part by regulating the expression of genes, such as lipl-4, with inverse effects on somatic maintenance and reproduction. We propose that AA could uncouple such germline to soma crosstalk, with beneficial implications for protein misfolding diseases.